1995
DOI: 10.1128/cmr.8.4.496-514.1995
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agent resistance in mycobacteria: molecular genetic insights.

Abstract: The knowledge acquired about drug resistance, then, will long remain of great practical value, and advances in the field will undoubtedly benefit the fight against tuberculosis considered on a worldwide scale.'' Georges Canetti J. Burns Amberson Lecture, 1965

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
158
0
23

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(190 citation statements)
references
References 39 publications
9
158
0
23
Order By: Relevance
“…In this sense, the genetic diversity characterising the rpoB mutations does not limit the performance of the method, and it is likely that the GeneChip array is also efficient in detecting minor mutations not represented in the collection of clinical isolates tested. The mutation frequencies found in the present study for the two positions 526 and 531 were similar to those reported previously by other investigators, and confirm that most (88%) of the substitutions occur in codons 526 and 531, which are associated generally with a high level of Rif R [2,15,19]. A deletion of the asparagine residue found at position 519 was identified in a Rif S isolate yielding c. 0.1% of resistant colonies; Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this sense, the genetic diversity characterising the rpoB mutations does not limit the performance of the method, and it is likely that the GeneChip array is also efficient in detecting minor mutations not represented in the collection of clinical isolates tested. The mutation frequencies found in the present study for the two positions 526 and 531 were similar to those reported previously by other investigators, and confirm that most (88%) of the substitutions occur in codons 526 and 531, which are associated generally with a high level of Rif R [2,15,19]. A deletion of the asparagine residue found at position 519 was identified in a Rif S isolate yielding c. 0.1% of resistant colonies; Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The genetic basis for Rif R in M. tuberculosis comprises mutations in the rpoB gene, which encodes the b-subunit of RNA polymerase [1,2]. The genetic changes leading to Rif R are now wellcharacterised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another topic of interest concerns the evolution of antibiotic resistance in the case of Mycobacterium tuberculosis (Mtb). The sole source of resistance to anti-TB drugs is by mutation of the target genes and no transferable antibiotic resistance plasmids have been found to encode resistance in Mtb: This pathogen seems to take care of antimicrobials quite nicely without participating in sex (Musser 1995).…”
Section: A Brief Historical Perspectivementioning
confidence: 99%
“…M. tuberculosis resistance to rifampicin is related to the mutations in a region of 81 base pairs of the gene rpoB which codes for the RNA polymerase sub-unit ␤ [39][40][41][42][43]. Isoniazid resistance is partly associated to a mutation of the gene katG which codes for a catalase-peroxidase and partly to a mutation of the regulator gene inhA [41,42].…”
Section: Tuberculosismentioning
confidence: 99%